Material Practices of Ethnographic Presence. (February 2021) - Laube, Stefan
Ethnographic research is a thoroughly material matter, but the involvement of material things in performing ethnographic methods is hardly investigated. Referring to my own research in various fields of digitalized work, I offer a reflexive analysis of the material production of ethnographic presence. In particular, I reflect on how clothing, field notes, and a camera contribute to making ethnographic research noticeable for and accessible to participants. Taking a practice theory perspective, the article conceptualizes ethnographic presence as a situated performance based on the dramaturgical and embodying contributions of material things. My analysis challenges the idea of openness as an ideal of research ethics that could be realized independently of the material and situated circumstances of fieldwork. It also shows that the material making of ethnographic presence offers particular methodological benefits including epistemic partnerships, insights from staged behavior, and the facilitation of ethnographic data collection.